Diagnostic values of BALF metagenomic next-generation sequencing, BALF real-time PCR and serum BDG for Pneumocystis jirovecii pneumonia in HIV-infected patients - Chen, Qianhui; Chen, Xiaoping; Mo, Pingzheng; Chen, Liangjun; Du, Qian; Hu, Wenjia; Jiang, Qunqun; Zhang, Zhongwei; Zhang, Yongxi; Guo, Qinglian; Xiong, Yong; Deng, Liping (Frontiers in Microbiology, 2024)
Introduction This study aimed to assess the diagnostic values of bronchoalveolar lavage fluid (BALF) real-time polymerase chain reaction (PCR) and BALF metagenomic next-generation sequencing (mNGS) for Pneumocystis jirovecii pneumonia (PJP) in patients infected with human immunodeficiency virus (HIV). Methods A total of 99 HIV-infected PJP patients and 61 HIV-infected patients diagnosed with non-PJP pneumonia between March 2019 and December 2022 were enrolled. P. jirovecii and multiple other co-pathogens detected in BALF by mNGS were analyzed. The clinical final diagnosis was employed as a benchmark. We compared the diagnostic performance of mNGS in PJP with serum BDG and BALF real-time PCR. The mixed infections detected by mNGS and modifications of antimicrobial treatment were also analyzed. Results The sensitivity of mNGS test of BALF samples reached 85.86%, which was significantly higher than serum BDG (39.39%, P < 0.001). The sensitivity of BALF P. jirovecii PCR (84.85%) was similar with mNGS (P > 0.05). The specificity of mNGS (100%) was also same as PCR (100.0%), and superior to serum BDG (88.52%, P < 0.001). Besides, mNGS performs remarkably well in identifying co-pathogens of PJP patients infected with HIV. In addition to P. jirovecii, 82 cases (82.83%) of other co-pathogens were identified based on mNGS. Moreover, thirty-four patients (34.34%) increased therapeutic dose of trimethoprim-sulfamethoxazole (TMP-SMZ) based on BALF P. jirovecii PCR. Based on the mNGS results, initial antimicrobial treatment was modified in 86.87% (86/99) of PJP patients. Conclusion BALF mNGS and real-time PCR are two powerful techniques for rapid diagnosis of PJP with high specificity and sensitivity. Moreover, the benefit of mNGS is that it may identify other organisms besides PJP and it may benefit proper and prompt treatment.